2015
DOI: 10.1155/2016/7241829
|View full text |Cite
|
Sign up to set email alerts
|

Periostin: A Downstream Mediator of EphB4‐Induced Osteogenic Differentiation of Human Bone Marrow‐Derived Mesenchymal Stem Cells

Abstract: Erythropoietin-producing hepatocyte B4 (EphB4) has been reported to be a key molecular switch in the regulation of bone homeostasis, but the underlying mechanism remains poorly understood. In this study, we investigated the role of EphB4 in regulating the expression of periostin (POSTN) within bone marrow-derived mesenchymal stem cells (MSCs) and assessed its effect and molecular mechanism of osteogenic induction in vitro. Treatment with ephrinB2-FC significantly increased the expression of POSTN in MSCs, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 42 publications
2
13
0
Order By: Relevance
“…In bone tissue, POSTN is preferentially expressed by periosteal osteoblasts in response to mechanical stimulation or parathyroid hormone (PTH), bone morphogenetic protein (BMP)-2, and transforming growth factor (TGF)-β, and it can regulate the osteogenic differentiation of osteoblasts to enhance bone formation 28 . Our pervious study also confirmed that the activation of erythropoietin-producing hepatocyte receptors (Eph) B4 up-regulates POSTN expression in MSCs and plays a crucial role in regulating bone homeostasis through an unknown mechanism 29 . A recent study reported that POSTN interacts with the Wnt/β-catenin signaling pathway indirectly by inhibiting sclerostin expression in bone 30 .…”
Section: Discussionsupporting
confidence: 65%
“…In bone tissue, POSTN is preferentially expressed by periosteal osteoblasts in response to mechanical stimulation or parathyroid hormone (PTH), bone morphogenetic protein (BMP)-2, and transforming growth factor (TGF)-β, and it can regulate the osteogenic differentiation of osteoblasts to enhance bone formation 28 . Our pervious study also confirmed that the activation of erythropoietin-producing hepatocyte receptors (Eph) B4 up-regulates POSTN expression in MSCs and plays a crucial role in regulating bone homeostasis through an unknown mechanism 29 . A recent study reported that POSTN interacts with the Wnt/β-catenin signaling pathway indirectly by inhibiting sclerostin expression in bone 30 .…”
Section: Discussionsupporting
confidence: 65%
“…The levels of total calcium, phosphorus, magnesium, and parathyroid hormone (PTH) were unaffected by BZDs [24,35] although some other results are controversial [45,46,47]. Interestingly, a report showed that midazolam could exert negative effects on cell viability and osteogenic differentiation of cultured human bone marrow stem cells, suggesting a detrimental effect of the use of midazolam on bone formation and growth [48] (Table 1). …”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, selecting the appropriate factor based on different reactivity of BM-MSCs to growth factors, to stimulate the proliferation, obtaining a higher proportion the mesenchymal stem cells has been regarded as a more accurate isolation method. Meanwhile, the new method of using 3 microns diameter plastic petri dish to screen BMMSCs, whose homogeneity are greater than 98%, with capacity of proliferation, self-renewal and have the potential to differentiate into bone, fat, cartilage tissue differentiation nature (6,(16)(17)(18)(19)(20). Overall, currently methods are various among laboratories in the world and further standardization of the BM-MSCs' separation process is still needed indepth study according to their biological characteristics and mechanisms.…”
mentioning
confidence: 99%